The Teaching of English Vocabulary to Young Learners in Beginner II Class at the Star English Course - Yendi Aditya R; Sri Wulandari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2021)
The aim of this study is to describe the teaching of English vocabulary to young learners in Beginner II class at the star English Pare. The research describes the tutor’s preparation that consists of syllabus, lesson plan, material, media, and technique; the tutor’s implementation that consists of: pre-teaching activity, main teaching activity, and post-teaching activity; and the assessment. The research subjects are: the director at The Star English Course, the tutor at The Star English Course, and the students of Beginner II class at The Star English Course. The research was analyzed by using descriptive qualitative method. The data were collected from observation, interview and documentation. In preparing for teaching English vocabulary to young learners at The Star English Course, the tutor has both syllabus and lesson plan. Moreover, the tutor is obligated to use media and game in delivering the material. It is really effective because children need an interesting media and fun activity in learning. During the pre-teaching activity, the tutor started the class by a warmer to prepare the students and help students to focus on the upcoming lessons. When teaching the main lesson, the tutor carried out the activity interactively and motivated the students to participate actively through the media and game. The post-teaching activity was done by making conclusions, reviewing, and giving assignments. The tutor’s assessment in teaching English vocabulary to young learners in beginner class at The Star English Course Pare is given in each meeting and there is one meeting in the end of the month for evaluation by giving final assessment that consist of material learned that month.